Assessment of the effect of cardiac rhythm and conduction disorders on the course and outcome of pregnancy: data of the Arrhythmia Center - M. A. Kirgizova; A. A. Dedkova; I. V. Kisteneva; E. V. Borisova; S. V. Popov (Российский кардиологический журнал, 2019)
Aim. To assess the effect of cardiac rhythm and conduction disorders on the course and outcome of pregnancy against the background of treatment.Material and methods. We analyzed 44 case histories of pregnant women examined in the department of surgical treatment of severe cardiac rhythm and conduction disorders during the period from 2012 to 2017 The patients’ age averaged 31,2±5,04 years. The survey was conducted during pregnancy from 12 to 37 weeks (average 28,0±6,4).Results. In most cases, rhythm disorders had idiopathic nature (57%), and in the remaining patients, diseases of the cardiovascular system were verified. Rhythm disorders before pregnancy were reported in 33 (75%) women. In two cases, ventricular tachycardia was hemodynamically significant. Therefore radiofrequency ablation was performed on 26 and 27 weeks of pregnancy. Radiofrequency ablation of supraventricular tachycardia was performed in three patients at the 27th, 29th and 31st week of pregnancy. One patient had an implanted pacemaker due to an atrioventricular block.Conclusion. Rhythm disorders observed in the patients did not require termination of the pregnancy. Antiarrhythmic therapy, prescribed for symptomatic, hemody-namically significant and life-threatening disorders, and surgical treatment made it possible to effectively manage pregnant women before delivery. Most patients had delivery on time, rhythm disorders in labor were not observed. Newborns had high Apgar scores.